Identifikasi Tata Ruang Rumah Tradisional Suku Lembak Kecamatan Pondok Kubang Kabupaten Bengkulu Tengah - Bella Meisyah Tri Utami; Mohammad Nur Dita Nugroho; Atik Prihatiningrum (EduInovasi: Journal of Basic Educational Studies, 2025)
This research aims to identify the spatial layout of traditional houses of the Lembak Tribe in Pondok Kubang Sub-district, Central Bengkulu Regency. Lembak traditional houses are one of the cultural heritages that reflect local values, both in social and architectural aspects. However, along with the times, the number of traditional houses is decreasing, so a study is needed to understand the spatial patterns and characteristics to support conservation efforts. The research method used was descriptive-qualitative with an ethnographic approach, involving field observations and in-depth interviews with house owners and local traditional leaders. The sample consisted of five traditional houses selected based on the criteria of building age above 80 years and still maintaining the original structure and spatial layout. The analysis was conducted by examining aspects of spatial zoning, function, and environmental factors that influence spatial patterns. The results showed that traditional houses of the Lembak Tribe have a spatial pattern consisting of public, semi-public, private and service zones. The main elements found include berande (front porch), luo (living room), Bilik Besak (main room), Bilik Kecik (children's room), Emben (kitchen and dining room), garang (washing place), and Garang panjang (side porch). The structure of the house is in the form of a stage with wooden pillars supported by stone, and the stairs are generally located on the right side of the building. This spatial pattern is influenced by cultural aspects and the geographical condition of the Bengkulu region, which is prone to earthquakes. This research contributes to providing an understanding of the spatial layout of traditional houses of the Lembak Tribe and serves as a reference for efforts to preserve vernacular architecture. The results of this study can also serve as a basis for traditional building conservation policies in the context of regional planning and cultural heritage.